2008
DOI: 10.1002/anie.200803434
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Single‐Component Trimerization and Polymerization Chromium Catalysts: The Role of the Metal Oxidation State

Abstract: One more trimer: A series of chromium complexes of different oxidation states are employed as catalysts for the polymerization/oligomerization of ethylene. The results suggest a link between chromium oxidation state and catalytic performance, with CrIII leading to oligomerization, CrII to polymerization, and CrI to selective trimerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
105
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 45 publications
3
105
0
Order By: Relevance
“…19,23 At this stage most of the evidence points towards a coordination arrangement such as shown in IV, in which the chloro group attached to aluminium acts as a third weak donor. Such an arrangement has been demonstrated by Gambarotta and co-workers in the case of Cr/pyrrole/ triethylaluminium (Phillips type) trimerisation catalysts, 42,43 as well as in other cases. 45 The highly selective nature of the PNPNH systems in conjunction with their long catalyst lifetime and the low cost of the co-catalyst make them of interest to industry, while their well-defined nature make them ideal for structural and mechanistic studies.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…19,23 At this stage most of the evidence points towards a coordination arrangement such as shown in IV, in which the chloro group attached to aluminium acts as a third weak donor. Such an arrangement has been demonstrated by Gambarotta and co-workers in the case of Cr/pyrrole/ triethylaluminium (Phillips type) trimerisation catalysts, 42,43 as well as in other cases. 45 The highly selective nature of the PNPNH systems in conjunction with their long catalyst lifetime and the low cost of the co-catalyst make them of interest to industry, while their well-defined nature make them ideal for structural and mechanistic studies.…”
Section: Introductionmentioning
confidence: 65%
“…Interestingly, in this report combinations of Cr(acac) 3 /PNPNH/AlEt 3 were shown to be completely inactive for catalysis, and as such the authors conclude that the active species most likely contains chloride; a result which is further supported by a subsequent structural study and is analogous to previously reported ethylene trimerisation systems. 33,34,[41][42][43][44] However, while there is no doubt that addition of a chloride source to the reaction mixture yields a positive result, previous reports by Rosenthal and co-workers have also demonstrated that catalytic mixtures containing no chloride can readily give high trimerisation activity and selectivity and as such the exact role of chloro groups in the catalytic mechanism remains unclear. 19,23 At this stage most of the evidence points towards a coordination arrangement such as shown in IV, in which the chloro group attached to aluminium acts as a third weak donor.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Unlike Sasols PNP-based and SK Energys PC 2 P-based catalysts, [3a,b] the current system shows a strong solvent and co-catalyst dependence. Selective ethylene tetramerization has only been observed in MeCy.…”
mentioning
confidence: 94%
“…For example, when highly reactive monovalent species are provided with a sufficiently long lifetime, selective oligomerization is initiated by the so-called redox reaction/ring-expansion mechanism. [2,5,7] As mentioned above, selective ethylene tetramerization remains exceedingly rare. With a maximum of around 77 % in the case of the process developed by SK Energy,…”
mentioning
confidence: 99%
See 1 more Smart Citation